2019
DOI: 10.2478/jwld-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and microbial contamination status of Madawachchiya, Padaviya and Kebithigollewa areas in Anuradhapura District, Sri Lanka

Abstract: Typhoid or enteric fever is a worldwide infection caused by the bacterium Salmonella enterica. In Sri Lanka, 12,823 Salmonella positive cases were recorded and 133 cases were recorded from Anuradhapura district during 2005 to 2014. Therefore, the study was carried out to identify the microbiological and chemical contamination status of forty-four water sources in Anuradhapura area during October 2016. The study was focused to determine total coliform, faecal coliform, Salmonella spp. and Shigella spp. contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…causes shigellosis due to consumption of pathogenic contaminated water [19]. Numerous studies have shown that microbial pathogens, such as Salmonella and E. coli are relatively stable in groundwater [28][29][30] and surface water [31][32][33][34] and the contamination prevalence depends upon the vulnerability of water sources to anthropological activities such as bathing, washing and defecating [33,34]. The results of the study showed the occurrence of Salmonella and Campylobacter in some ground and surface water sources which may alarm possible root causes of susceptibility of gastrointestinal disease of people who consume contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…causes shigellosis due to consumption of pathogenic contaminated water [19]. Numerous studies have shown that microbial pathogens, such as Salmonella and E. coli are relatively stable in groundwater [28][29][30] and surface water [31][32][33][34] and the contamination prevalence depends upon the vulnerability of water sources to anthropological activities such as bathing, washing and defecating [33,34]. The results of the study showed the occurrence of Salmonella and Campylobacter in some ground and surface water sources which may alarm possible root causes of susceptibility of gastrointestinal disease of people who consume contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pH values in the Medawachchiya and Galnewa areas were within the allowable range for drinking (Imbulana et al 2020). The pH values in springs were found to be lower than those recommended by the World Health Organization and the SLSI for drinking water quality (Mahagamage and Manage 2019). Except for one ground well in Padaviya, all ground wells had pH levels within the SLSI's maximum permissible range (Mahagamage and Manage, 2019).…”
Section: General Water Quality Parameters In Dug Well and Spring Watermentioning
confidence: 75%
“…The pH values in springs were found to be lower than those recommended by the World Health Organization and the SLSI for drinking water quality (Mahagamage and Manage 2019). Except for one ground well in Padaviya, all ground wells had pH levels within the SLSI's maximum permissible range (Mahagamage and Manage, 2019). The average pH of Girandurukotte's groundwater varied between 6.56 and 7.22 (Kumari et al 2016).…”
Section: General Water Quality Parameters In Dug Well and Spring Watermentioning
confidence: 84%
See 1 more Smart Citation
“…The quality of the water is the major indicator to determine human health, mainly in populated areas where have a high risk to receive a multitude of contaminants such as antibiotics, heavy metals, organic wastes, and xenobiotics (Qadir et al, 2008 ; Mahagamage & Manage, 2015 ). In Sri Lanka, 29% populations only get pipe-borne water facilities where day by day water requirement including drinking is fulfilled from groundwater, river, springs, and streams (CEA, 2017 ; Mahagamage & Manage, 2019 ).…”
Section: Introductionmentioning
confidence: 99%